Brown rice consumption and changes in the metabolic risk factors of non-communicable diseases in selected overweight and obese Filipinos - Laborde, Gladys Mae R.; Estrada, Miriam R.; Romero, Marissa V. (Vol. 150, No.2 (April 2021), pages 461-471.)
"Human studies on the health benefits of brown rice (BR) are limited, especially in the Philippines, even though rice is the staple food. This is the first randomized controlled investigation on the effects of BR consumption on metabolic risk factors of non-communicable diseases (NCDs) in selected overweight and obese Filipino adults. Out of 60 eligible male and female participants (30-59 yr old) randomly assigned to the BR and white rice (WR) groups, 52 completed the study. This was organized in a semi-free-living condition with 6-wk dietary intervention and 6-wk follow-up"- title page.